Riconsiderare il Concordato del 1929: Noterelle di uno storico della política - Pombeni, Paolo (Annali di storia dell'esegesi, 2019)
In the Concordat of 1929 the main result obtained by the Holy See was the recognition of the central role of the Catholic religion in the construction of the civil and political identity of the nation. The defense of the principle of the Catholic religion as the religion of almost all the Italian population would have lasted for a long time. He had in his support the undoubted spread of religious practices in accompaniment to the fundamental passages of people’s lives (baptisms, first communions, marriages, funerals), though they were lived more and more as rituals of passage rather than as conscious adhesions to a universe of faith. However, it was enough to support the myth of the ‘Catholic nation,’ which was accepted in this way even into formally secular political sectors.